THE INFLUENCE OF CIVIL SOCIETY ON THE EFFECTIVENESS OF THE INFORMATION POLICY OF THE STATE DURING THE PERIOD OF WAR - Cherevatiuk, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose of the article: to analyze the influence of civil society on the effectiveness of the information policy of the state during the period of full-scale aggression. Methods: general and scientific and special and legal methods of scientific knowledge, namely: systemic and structural and functional methods, method of observation, method of generalization, methods of analysis and synthesis have been applied. Results: ensuring the effective information policy in the extremely difficult conditions of the war led to the actualization of the theoretical consideration, including issues of interaction between the institutions of state power and the institutions of civil society. An author examines the institutional phenomenon of their interaction in ensuring the effective information policy. Discussion: the fundamental prerequisite for the formation and modern mechanisms of interaction between state institutions and civil society is the gradual implementation at the state level of successful public initiatives and programs. The state’s monopoly on functions that may belong to civil society institutions is controversial. The activity of civil society institutions in the information security sector is especially important, which is primarily due to the fact that the state has a small amount of resources to counter the threats and challenges that appear in this area. Civil institutions, at a sufficiently high level of political culture and a perfect regulatory base, are important allies of the state in the modern information war. In the period of a full-scale war, the fact that the resources of the power (in the form of the government, executive structures, parliament, president, etc.) are not enough to effectively protect the country’s information space from external and internal risks seems even more obvious. Thus, the power structures are forced to turn for help to public organizations and institutions, which often act as a strategic ally of the state. First of all, we are talking about public organizations, unions, movements, non-governmental groups, think tanks, mass media, etc.